Antibody response to the 23-valent pneumococcal polysaccharide vaccine after conjugate vaccine in patients with chronic lymphocytic leukemia - Vesa Lindström; Janne Aittoniemi; Urpu Salmenniemi; Helena Käyhty; Heini Huhtala; Marjatta Sinisalo (Taylor & Francis Group, 2019)
The 23-valent pneumococcal polysaccharide vaccine (PPV23) given alone is ineffective in patients with chronic lymphocytic leukemia (CLL) and better antibody response is achieved with pneumococcal conjugate vaccines (PCVs). In this study, we determine whether CLL patients would achieve a significant antibody response and broaden their serotype coverage against invasive pneumococcal disease (IPD) with PPV23 given five years after the 7-valent conjugate vaccine (PCV7). A total of 24 patients with CLL and eight controls were vaccinated with PPV23 five years after PCV7. Blood samples for evaluation of antibody response to PCV7 serotypes and PPV23 serotypes 5 and 7 were taken before vaccination and one month after it. Post-vaccination samples were available from 20 patients. IgG antibodies were measured with ELISA. Antibody concentrations after PPV23 were significantly lower in CLL patients for six of the PCV7 serotypes and for both PPV23 serotypes. Only 10% to 15% of CLL patients achieved an antibody response suggested to be protective against IPD. Hence, PCV7 given five years before PPV23 did not improve antibody response in patients with CLL. Based on our results, PPV23 given after a PCV primer is not useful against IPD in CLL patients.